PHARMACEUTICO ANALYTICAL STUDY AND COMPARATIVE ANTIMICROBIAL EFFECT OF HARTALA BHASMA AND HARTALAGODANTI BHASMA - Lokesh Kumar, Garg; Mahendra, Singh; Richa, Singh; Rajesh, Dhaked (International Journal of Ayurveda and Pharma Research, 2015)
Hartala (Orpiment) is a deep orange-yellow colored mineral with formula As2S3 and Godanti (Gypsum) is a very soft sulfate mineral with the chemical formula CaSO4 2H2O. Hartala bhasma and Hartalagodanti bhasma is being in practice widely in Ayurvedic formulation in spite of its toxic nature. This study includes, Sodhan (purification) of Haratala and Godanti, Marana of Hartala, Godanti and Hartalagodanti, Chemical Analysis of Hartala bhasma and Hartalagodanti bhasma and Comparative antimicrobial study of Hartala bhasma and Hartalagodanti bhasma. Antimicrobial activity of Hartala bhasma and Hartalagodanti bhasma was conducted against gram positive, gram negative bacteria to evaluate its efficacy as broad spectrum antibiotic. So an attempt had been made to put Hartala bhasma and Hartalagodanti bhasma as an antimicrobial agent. Hartala bhasma and Hartalagodanti bhasma has an effective antimicrobial activity against Streptococcus pneumoniae, Klebsiella pneumoniae, Pseudomonas aeruginosa and Staphylococcus aureus in both Diffusion methods (Kirby- Bauer disc diffusion method and Stokes disc diffusion method) and Dilution methods (Broth dilution method & Agar dilution method).